SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN GURU BERBASIS WEB DENGAN METODE SIMPLE ADDITIVE WEIGHTING - Hidayat, Radi; Ariadi, Fadly (JUPIK : Jurnal Penelitian Ilmu komputer, 2023)
PT. Impian Semesta Raya is one of the Indonesian course places for foreigners. This course provides assistance to customers in order to get more optimal learning outcomes or preparations. By attending the course, customers will be able to adjust to the educational situation they are facing. Many foreigners, especially Japanese people, want to apply to study, so these courses often select new teachers who match the criteria that Japanese people want. Decision Support System for the selection of new teachers with the Simple Additive Weighting (SAW) method in this course. This research will help admins in managing criteria, to perform calculations with the Simple Additive Weighting (SAW) method. The criteria set in this application are the suitability of the location of the new teacher, teaching experience of the new teacher, mastery and proficient in learning methods, age, and mastery of the Japanese language. From the results of the selection of new teachers, it will be sorted based on the total calculation of the highest score using the Simple Additive Weighting (SAW) method. The results of the implementation in building a web-based teacher recruitment decision support system (SPK) with the Simple Additive Weighting (SAW) method that has been successfully implemented at PT Impian Semesta Raya is an important breakthrough in a more efficient and objective teacher selection process. The results of this Decision Support System rank first on teacher candidates with the largest Preference Value (Vi). As for this study, the largest Preference (Vi) value is Yuli Purnama Sari (V2) with a value of 0.893.